Self-medication of Ayurvedic Medicine Associated with Fatal Toxic Epidermal Necrolysis: A Case Report - Jangra, Manjeet S.; Chhabra, Manik; Bhagavathula, Akshaya Srikanth (Current Traditional Medicine, 2020)
Introduction: Ayurveda is one of the most renowned traditional systems of medicine and is widely practiced in India. Self-medication of these ayurvedic medicines (AM’s) may elicit more or less similar type of adverse reactions as synthetic drugs. Methods: We present a case report on toxic epidermal necrolysis due to self-medication of ayurvedic medicine. Case Report: The present case is of a patient who used Singhnad Guggulu for 20 days and developed Steven-Johnson Syndrome (SJS) followed by toxic epidermal necrolysis (TEN). The patient was treated with steroids and antihistamines. The patient recovered completely following seven days of treatment and discharged. Results: After ruling out the provisional diagnosis, the patient was diagnosed with druginduced SJS/TEN. The World Health Organization-Uppsala Monitoring Center (WHOUMC) causality assessment scale was used by taking into consideration the temporal relationship and other relevant parameters and adverse drug reaction (ADR) was found to be ‘certain’. Conclusion: To our knowledge, the present case study is the first report of SJS/TEN that was caused by “Singhnad Guggulu” suggesting clinicians to be vigilant about the possibility of SJS/TEN occurrences with AM. Also, consumers should be advised to use these drugs only on the prescription of the institutionally qualified ayurvedic practitioners.
Keywords: Ayurveda